1974
DOI: 10.5636/jgg.26.329
|View full text |Cite
|
Sign up to set email alerts
|

Moessbauer effect observations of the "X-phase" in the ilmenite-hematite series.

Abstract: Preliminary Mossbauer spectroscopy data support the "x-phase" theory of Ishikawa and Syono, which explains reversed thermoremanent magnetization in the ilmenite-hematite series. Heat-treated samples of 50, 55, and 60 mole % ilmenite show long-range magnetic order above their Curie points; quenched samples do not. The "x-phase" constitutes about seven percent of the 60 mole % sample. Part of the x-phase has a Curie temperature at least 200C higher than the bulk sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…Hoffman supports this contention by presenting good evidence that the x-phase has a narrowly restricted Curie temperature near 350~ an observation consistent with the x-phase being a hematite-rich exsolved phase with roughly 40 mole 70 ilmenite in solid solution. This is consistent with the work of Allan and Shive (1974), who use M6ssbauer analysis to find that at least part of the x-phase has a Curie temperature close to the 350~ temperature cited by Hoffman. However, Hoffman (1975) also indicated that his mechanism will work only if the temperature of the solvus in the vicinity of y--0.5 to y = 0.6 is far higher than that allowed by Lindsley (1973).…”
Section: Self-reversal In Titanohematitessupporting
confidence: 79%
“…Hoffman supports this contention by presenting good evidence that the x-phase has a narrowly restricted Curie temperature near 350~ an observation consistent with the x-phase being a hematite-rich exsolved phase with roughly 40 mole 70 ilmenite in solid solution. This is consistent with the work of Allan and Shive (1974), who use M6ssbauer analysis to find that at least part of the x-phase has a Curie temperature close to the 350~ temperature cited by Hoffman. However, Hoffman (1975) also indicated that his mechanism will work only if the temperature of the solvus in the vicinity of y--0.5 to y = 0.6 is far higher than that allowed by Lindsley (1973).…”
Section: Self-reversal In Titanohematitessupporting
confidence: 79%
“…8), and that they may be as small as a few atoms across in some cases (Lawson et al 1981;Lawson & Nord 1984;Nord & Lawson 1989). The possibility of a self-reversed thermal remanent magnetization (TRM) within ferrian ilmenites (Ishikawa & Syono 1963;Allen & Shive 1974;Lawson et al 1981;Lawson & Nord 1984;Nord & Lawson 1989;Hoffman 1992) is not directly relevant in the present study because, as detrital particles, the dominant remanence component, which might have been originally self-reversed, would align with the ambient geomagnetic field in the depositional environment. Although the grains identified as the likely remanence carriers in this study have somewhat higher Ti (and Mn) contents than those in the above-cited studies, the magnetic properties of the ilmenite grains in the Wanganui basin sediments can be attributed to a similar mechanism to that discussed by Lawson & Nord (t984) and Nord & Lawson (1989).…”
Section: Reconciling the Apparent Conflict Between Magnetic Behaviourmentioning
confidence: 97%